2019
DOI: 10.1088/1742-6596/1390/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Prospect for top quark FCNC searches at the FCC-hh

Abstract: FCC-hh is a proposed future energy-frontier hadron collider, which goal is to provide high luminosity proton collisions at a centre-of-mass energy of 100 TeV. The FCC-hh has an extremely rich physics program ranging from standard model (SM) measurements to direct searches for physics beyond the standard model (BSM). One of the processes sensitive to new physics is flavour-changing neutral currents (FCNC) that extremely rare in the SM but have enhanced behavior in several BSM scenarios. In this report we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…At present there is no any experimental evidence of the FCNC process. One can expect that future research and improvements on these bounds with the proposed higher center-of-mass energy colliders [25], such as High Energy LHC (HE-LHC) with 27 TeV c.m. energy [26] and Future Circular Collider in hadron-hadron mode (FCC-hh) with 100 TeV c.m.…”
Section: Introductionmentioning
confidence: 99%
“…At present there is no any experimental evidence of the FCNC process. One can expect that future research and improvements on these bounds with the proposed higher center-of-mass energy colliders [25], such as High Energy LHC (HE-LHC) with 27 TeV c.m. energy [26] and Future Circular Collider in hadron-hadron mode (FCC-hh) with 100 TeV c.m.…”
Section: Introductionmentioning
confidence: 99%
“…The rough estimation by Backovic et al [44] has shown that it is challenging to observe the T quark with the diphoton decay channel at the 14 TeV LHC due to the small production cross section. In recent years, the proposed higher center-of-mass energy colliders have been discussed worldwide [72,74,76], such as High Energy Fig. 1 The Feynman diagrams for the process pp → Tb j LHC (HE-LHC) with 27 TeV c.m.…”
Section: Introductionmentioning
confidence: 99%
“…One can expect to improve further these limits at higher c.m. energies [46]. The future High Energy LHC (HE-LHC) with 27 TeV c.m.…”
Section: Introductionmentioning
confidence: 99%